2023
DOI: 10.1002/hsr2.1045
|View full text |Cite
|
Sign up to set email alerts
|

An oral French maritime pine bark extract improves hair density in menopausal women: A randomized, placebo‐controlled, double blind intervention study

Abstract: Background and Aims Female pattern hair loss affects females of all ages with a trend to increase after menopause. This disorder may have significant psychological impact and lead to anxiety and depression. Objective In a single center, double blind, randomized, placebo‐controlled study, the effects of oral Pycnogenol® intake (3 × 50 mg/day for a total of 6 months) on hair density, scalp microcirculation, and a variety of skin physiological parameters was studied in Han Chinese menopausal women (N = 76) in Sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Pycnogenol R 's favorable impact on blood circulation was demonstrated in multiple ways, like the improvement of endothelial function or microcirculation in clinical RDP trials on cardiovascular health, chronic venous insufficiency, on skin and hair health, eye health and menopause (9, 11, 12, 20-22, 28-33, 43-47). Improved skin elasticity, skin moisture, joint flexibility and hair health illustrate the beneficial effects of Pycnogenol R on the extracellular matrix, observed in RDP studies (40)(41)(42)(43)(44). The complementarity of these mechanisms justifies Pycnogenol R 's positive effects on its largely diversified areas of application.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Pycnogenol R 's favorable impact on blood circulation was demonstrated in multiple ways, like the improvement of endothelial function or microcirculation in clinical RDP trials on cardiovascular health, chronic venous insufficiency, on skin and hair health, eye health and menopause (9, 11, 12, 20-22, 28-33, 43-47). Improved skin elasticity, skin moisture, joint flexibility and hair health illustrate the beneficial effects of Pycnogenol R on the extracellular matrix, observed in RDP studies (40)(41)(42)(43)(44). The complementarity of these mechanisms justifies Pycnogenol R 's positive effects on its largely diversified areas of application.…”
Section: Discussionmentioning
confidence: 92%
“…A study on skin health and one recently published study on hair quality have shown Pycnogenol ® ’s effects on beauty and skin health in RDP setups ( 43 , 44 ).…”
Section: Randomized Double-blind Placebo-controlled Human Clinical St...mentioning
confidence: 99%
See 2 more Smart Citations
“…While the supplementation during 6 months with the blend showed a significant reduction in the number of hairs removed in the pull test, the study did not report any beneficial effect on hair growth. Additionally, a French pine bark extract, rich in proanthocyanidins, was recently reported to clinically improve total hair density in Chinese menopausal women following a 6-month supplementation, but without mentioning if the supplementation specifically improved anagen hair density and therefore hair growth [36].…”
Section: Discussionmentioning
confidence: 99%